Nanomaterials with high solar reflectance as an emerging path towards energy-efficient envelope systems: a review - Veloso, RC (2021)
The application of nanomaterials in the construction field is allowing the development of smart, green, durable and more efficient buildings. Among the most widely researched nanomaterials are nanosized cool pigments, which are being enforced to achieve thermal and energy-efficient facades, with the development of high reflectance and retro-reflectance coatings. Their peculiar optical and catalytic activity turns nanomaterials into suitable candidates to be used as dark coloured high solar reflectance without affecting aesthetic characteristics, thus improving the durability of coatings. The objective of this paper is to review the state-of-the-art on the benefits of using high reflectance nanopigments as coatings in building facades and their production and synthesis processes. It is thus divided into three main topics: (i) the benefits of using nanopigments on facades, (ii) the most important nanomaterials used as cool pigments and (iii) the main methods of synthesizing nanopigments. One expects that the study of near-infrared nanopigmentation synthesis processes will be able to promote and disseminate the use of nanotechnology in construction, assessing the production problems and limitation and thus helping to disseminate new products by reducing production costs and increase availability. [GRAPHICS] .